Chronic Uterine Dehiscence Secondary to Genitourinary Tuberculosis: A Case Report - Roberts, Kasey; Buchenroth, Britta; Novi, Joseph (Translation: The University of Toledo Journal of Medical Sciences, 2018)
Background: Genitourinary tuberculosis (GU TB) most commonly presents as infertility, pelvic pain, or menstrual irregularities in patients from countries where the disease continues to be endemic. Case: A 27 year-old G1P1001 from western Asia presented to our institution’s urogynecology office for management of pelvic pain secondary to known uterine dehiscence. The patient underwent a laparotomy for repair of the dehiscence. During the procedure she was noted to have a large, white mass within the uterine dehiscence that was later determined to likely be GU TB. The patient was referred to the Health Department where she received one year of anti-TB treatment. Conclusion: GU TB should be considered in the differential diagnosis of uterine dehiscence in patients from countries where the disease remains endemic.